Talking about the World Press Photo 20 Exhibition at the WestLicht: Analysing Communication Frames on Social Media. (2nd January 2021) - Melcher, Sabrina; Zuanni, Chiara
Abstract : Developments in the digital field have introduced new opportunities not only for museums to engage with their visitors, but also for researchers to learn about visitors' experiences through their online behaviour. This article discusses how the mediation and perception of exhibited photographs in museums can be researched through an analysis of Instagram posts, using text-mining methods. A case study examining the World Press Photo 20 exhibition at the WestLicht museum in Vienna was used to explore three different framings of the World Press photos: first, how the photographs were initially used within newspaper articles as a news source; second, how the museum communicated the exhibited photos on social media; and third, how visitors reflected on the exhibition and the museum visit on Instagram.